The association of dietary resistance starch intake with all-cause and cause-specific mortality - Wan, Jiang; Li, Xiaocong; Gu, Ming; Li, Qi; Wang, Chuyun; Yuan, Run; Li, Lin; Li, Xiang; Ye, Shaodong; Chen, Jichun (Frontiers in Nutrition, 2022)
Background: Several studies have estimated daily intake of resistant starch (RS), but no studies have investigated the relationship of RS intake with mortality. Objective: We aimed to examine associations between RS intake and all-cause and cause-specific mortality. Methods: Data from US National Health and Nutrition Examination Survey from 1999 to 2018 with 24-hour dietary recall data was used in current study. The main exposure in this study was resistant starch intake and the main outcome was the mortality status of participants until December 31, 2019. The multivariable Cox proportional hazards regression models were developed to evaluate the hazard ratios (HRs) and 95% confidence interval (95% CI) of cardiovascular disease (CVD), cancer, and all-cause mortality associated with RS intake. Results: A total of 42,586 US adults (mean [SD] age, 46.91[16.88] years; 22,328 [52.43%] female) were included in the present analysis. During the 454,252 person-years of follow-up, 7,043 all-cause deaths occurred, including 1,809 deaths from CVD and 1,574 deaths from cancer. The multivariable-adjusted hazard ratios (HRs) for CVD, cancer and all-cause mortality per quintile increase in RS intake were 1 (95%CI, 0.97-1.04), 0.96 (95%CI, 0.93-1) and 0.96 (95%CI, 0.95-0.98), respectively. The associations remained similar in the subgroup and sensitivity analyses. Conclusion: Higher RS intake is significantly associated with lower cancer and all-cause mortality, but not significantly with CVD mortality. Future studies focusing on other populations with different food sources of RS and RS subtypes are needed to access the dose-response relationship and to improve global dietary recommendations.